2020
DOI: 10.1111/pedi.12984
|View full text |Cite
|
Sign up to set email alerts
|

Trend of type 1 diabetes incidence in children between 2009 and 2019 in Elazig, Turkey

Abstract: Objective: To assess the incidence of T1D in children aged <15 years in Elazig, Turkey.Method: The data of children who have been registered as child with T1D in the database of pediatric diabetes clinic was analyzed. Childhood census data were acquired from the Turkish Statistical Institute. The incidence rates of T1D were calculated for the whole group as well as separately for age group, gender, year of diagnosis, and place of residence, viz. either urban or rural per 100 000 persons per year.The change of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
0
10
2
1
Order By: Relevance
“… 24 In a study examining the years 2009 to 2019 in Elazığ, it was observed that the increasing trend in the incidence of T1D was especially in boys, urban residents, and children between the ages of 5 and 9 years. 25 In another study examining newly diagnosed T1D cases in Elazığ between 2016 and 2019, it was observed that the presence of DKA at the time of diagnosis was associated with high HbA1c levels, and that presentation with severe DKA was associated with people living in rural areas and low education levels of mothers. 26 Newly diagnosed T1D cases examined in tertiary care in the Southern region of Turkey between 2019 and 2021 were compared as 2 groups before and after the pandemic, and it was found that the frequency of severe DKA was higher in cases diagnosed after the pandemic, and antibody positivity for celiac disease and glutamic acid decarboxylase were observed more common.…”
Section: Discussionmentioning
confidence: 98%
“… 24 In a study examining the years 2009 to 2019 in Elazığ, it was observed that the increasing trend in the incidence of T1D was especially in boys, urban residents, and children between the ages of 5 and 9 years. 25 In another study examining newly diagnosed T1D cases in Elazığ between 2016 and 2019, it was observed that the presence of DKA at the time of diagnosis was associated with high HbA1c levels, and that presentation with severe DKA was associated with people living in rural areas and low education levels of mothers. 26 Newly diagnosed T1D cases examined in tertiary care in the Southern region of Turkey between 2019 and 2021 were compared as 2 groups before and after the pandemic, and it was found that the frequency of severe DKA was higher in cases diagnosed after the pandemic, and antibody positivity for celiac disease and glutamic acid decarboxylase were observed more common.…”
Section: Discussionmentioning
confidence: 98%
“…The reported incidence rate in Turkey was higher than in the present study. This might be due to the studied age group 23 . We included children aged <20 years, and the rate in children aged 15–19 years is lower than children aged 5–15 years.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the mean age of diagnosis was 9.89 years, which was higher than that reported in the study of Esen et al . in Turkey 23 .…”
Section: Discussionmentioning
confidence: 99%
“…It is predicted that by 2030, this figure would rise to 578 million, or 10.2% of the adult population worldwide, and that by 2045, it will reach 700 million, or 10.9% of the adult population worldwide. The estimated prevalence of diabetes in men and women worldwide in 2019 is 9.6% and 9.0%, respectively, for the total population of each gender (Esen and Okdemir, 2020). Additionally, an estimated 4.2 million adults aged 20 to 99 died from diabetes-related complications in 2019, and the cost of treating diabetes-related health issues is anticipated to be at least 760 billion USD, or 10% of all spending on adults (Banday et al, 2020).…”
Section: Diabetesmentioning
confidence: 99%